Mindfulness Yoga: Pelatihan Optimalisasi Kesehatan Fisik dan Kesejahteraan Psikologi bagi Lansia - Laila Indra Lestari; Raissa Dwifandra Putri; Rizka Fibria Nugrahani; Erianto Fanani; Aufa Angga Wimaswara (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2026)
Indonesia is undergoing a demographic shift marked by a rising proportion of elderly individuals, a trend that is also evident in Malang Regency. A needs assessment conducted among elderly residents of PKK Perum Sengkaling Indah 1 RW 08 identified various physical and psychological health declines that adversely affect their psychological well-being. Mindfulness Yoga was introduced as a strategic intervention aimed at optimizing both physical and psychological health among the elderly. The program was implemented using a structured and systematic approach, comprising three phases: (1) initial preparation, (2) intervention delivery, and (3) final evaluation. Effectiveness of the intervention was assessed through pre-test and post-test measurements. Results indicated a statistically significant improvement in participants’ psychological well-being following two intensive sessions of Mindfulness Yoga (Wilcoxon W = 0.00; p = 0.002). These findings support the feasibility of implementing the program within elderly community settings and highlight its potential for replication in other regions.